Pembelajaran PAKEM Berbasis Media Audio Visual Gerak dalam Melatih Konsentrasi Belajar Anak di TPA Sahabat Hati Pontianak - Ulfa, Maria (Al-Athfal: Jurnal Pendidikan Anak, 2019)
Early age is an important age to influence subsequent developments. Early childhood is a period of play as a way of learning children. One model of learning in early childhood is PAKEM learning (Active, Creative, Effective and Enjoyable Learning). The purpose of this study is to present PAKEM learning based on audio-visual motion media in training children's learning concentration. The method used is qualitative descriptive with data collection techniques in the form of interviews, observation and documentation. In analyzing the data, it used the Miles and Huberman model. The validity test of the data used source and technique triangulation. The results showed that PAKEM learning based on audio visual motion in the TPA Sahabat Hati was carried out through several stages, namely, planning, implementation and evaluation. The implementation is an initial activity, core and closing. Audio visual motion is displayed via television which is arranged according to the learning schedule. Children then are active to see, hear and follow their movements directly. Thus, PAKEM learning based on audio-visual motion media at the TPA Sahabat Hati is effective in training children's learning concentration.